Sistem Informasi Promosi Berbasis Web Pada CV. Indoestri Supply - Nurhaliza, Tiko; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2023)
CV. Indoestri Supply is a company that sells Thaitea beverage equipment. Problems were found, namely: the promotion process using conventional promotion through the installation of banners, word of mouth promotion, and added to promotion through social media advertising. The purpose of this research is to analyze and design a web-based promotional information system. The research method uses a prototype model and a UML model, using use case diagrams, activity diagrams, and class diagrams. The results of this study are a prototype of a web-based promotional information system that can help CV. Indoestri Supply in overcoming the problems faced.